Zjawisko technostresu w pracy – przegląd koncepcji badawczych z perspektywy badań pracowników zdalnych - Dudek, Aleksandra (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2024)
This article addresses the problem of technostress in remote work. It has a special character due to the wide scope of the issue and its interdisciplinarity, as well as the context – the dynamic development of modern technologies and their impact on the sphere of work. This article aims to determine the problems related to the development of the concept of technostress in remote work and its application in sociological research. The source material used was scientific literature and publications presenting the results of social research on technostress and original research. The literature review made it possible to describe the definition of technostress and related key categories (technostress creators, inhibitors), as well as research areas, approaches and results. Then, the proposed concept of researching technostress at work was discussed, including its conceptualization and elements of operationalization. The methodology of the original research was developed within the framework of a quantitative approach: a survey method was used (CAWI, a highly standardized questionnaire). The project was implemented in 2023 and covered office employees (accountants) working remotely. Despite its limitations, these studies provided interesting data on technostress, including the areas most affected (pace of work, task load, constant connection with the workplace). Technostress factors were identified (type of position, frequency of remote work, form of employment) and factors that are most important in relieving stress (high level of digital competences, satisfying work).